Numerical simulation of cold forming of a-titanium alloy sheets - Jurendić, Sebastijan (Strojniški vestnik, 2013)
Despite the generally good cold workability of some -titanium alloys, their relevant mechanical properties are quite different to those of traditional cold forming materials. The hexagonal close packed (HCP) crystal structure of -titanium alloys results in a highly textured, highly anisotropic material that exhibits some specifics in its plastic response. A numerical simulation method using the Barlat 1989 material model has been developed to aid in forming tool development and process parameter determination. In order to account for the anisotropic hardening of the material, plastic strain ratios are input into the model as functions of plastic strain and an inversely determined, experimental strain hardening curve is used. The procedure for determining the input data from the tensile test is outlined and demonstrated on the -titanium alloy 1.2ASN from Kobe Steel. The flow potential exponent m is evaluated via a parametric analysis of the Erichsen test and an appropriate value is determined. The forming limit diagram is adopted as a means for failure prediction and determined using the Nakajima method. Finally, the method is evaluated on an example of a deep drawn part with good correlation to the physical process.
Keywords: alfa-titan; alpha-titanium; anisotropy; anizotropija; cold forming; deep drawing; globoki vlek; HCP metals; heksagonalna kristalna struktura; numerical simulation; numerična simulacija; preoblikovanje v hladnem